A Study of Adolescents’ Anxiety and Achievement in English as a Foreign Language - Eka Christyani; Dede Rohadi Fajri; Sisca Wulansari Saputri (FKIP, Universitas Banten Jaya, 2022)
The purpose of this study was to determine the anxiety of adolescents, especially in Mardi Yuana Junior High School students, Serang City, and their achievements in the process of learning English as a foreign language in foreign language classes. This research is qualitative research with a descriptive approach through questionnaire observations, interviews, and documentation. The results of this study indicate that 2 students feel anxious with a percentage of 5.88%, 20 students feel mildly anxious with a percentage of 58.82%, 12 students feel relaxed with a percentage of 35.29%, 0 students feel relaxed/very relaxed with a percentage of 0%. So it could be concluded that the factors that could affect the students' anxiety in learning English as a foreign language are internal and external. Internal factors include perception, personality, and intelligence. While external factors include motivation, classroom environment, and cognitive. As for what affects students' achievement in learning English as a foreign language, they are afraid of being given a negative evaluation, when they make mistakes and are afraid of being laughed at by their classmates, it makes them afraid to explore themselves further about foreign language learning. Therefore, anxiety in learning English should at least motivate students, especially in their teens so that they can learn foreign languages well.